Psychological testing history, principles, and applications - Gregory, Robert J. (Boston Allyn and Bacon, 1996)
In addition to customary coverage of traditional topics and instruments, the author provides detailed presentations for several topics not always found in other textbooks. These topics include: history of psychological testing, early uses and abuses of intelligence, neuropsychological foundations of ability, factor analysis, assessment of learning disabilities, consumer assessment, environmental assessment, and courtroom testimony.
The history of psychological testing -- The origins of psychological testing -- The importance of testing -- The consequences of test results -- Rudimentary forms of testing in China in 2200 B.C. -- Psychiatric antecedents of psychological testing -- The brass instruments era of testing -- Changing conceptions of mental retardation in the 1800s -- Influence of Binet's early research upon his test -- Binet and testing for higher mental processes -- The revised scales and the advent of IQ -- Early testing in the United States -- Early uses and abuses of tests in America -- The invention of nonverbal tests in the early 1900s -- The Stanford-Binet : the early mainstay of IQ -- Group tests and the classification of WWI Army recruits -- Early educational testing -- The development of aptitude tests -- Personality and vocational testing after WWI -- The origins of projective testing -- The development of interest inventories -- Summary of major landmarks in the history of testing -- Tests and the testing process -- The nature and uses of psychological tests -- Definition of a test -- Further distinctions in testing -- Types of tests -- Uses of testing -- Who may obtain tests -- Sources of information on tests -- The testing process -- Standardized procedures in test administration -- The impact of nonstandard testing -- Desirable procedures of test administration -- Influence of the examiner -- Background and motivation of the examinee -- Issues in scoring -- Norms and reliability -- Norms and test standardization.
Keywords: Psychological tests; Psychological tests -- History